Electrophoretically Deposited Layers of Octahedral Molybdenum Cluster Complexes: A Promising Coating for Mitigation of Pathogenic Bacterial Biofilms under Blue Light - Kirakci, Kaplan; Nguyen, Thi Kim Ngan; Grasset, Fabien; Uchikoshi, Tetsuo; Zelenka, Jaroslav; Kubát, Pavel; Ruml, Tomáš; Lang, Kamil (ACS applied materials & interfaces, 2020)
The fight against infective microorganisms is becoming a worldwide priority due to serious concerns about the rising numbers of drug-resistant pathogenic bacteria. In this context, the inactivation of pathogens by singlet oxygen, O2(1Δg), produced by photosensitizers upon light irradiation has become an attractive strategy to combat drug-resistant microbes. To achieve this goal, we electrophoretically deposited O2(1Δg)-photosensitizing octahedral molybdenum cluster complexes on indium-tin oxide-coated glass plates. This procedure led to the first example of molecular photosensitizer layers able to photoinactivate bacterial biofilms. We delineated the morphology, composition, luminescence, and singlet oxygen formation of these layers and correlated these features with their antibacterial activity. Clearly, continuous 460 nm light irradiation imparted the layers with strong antibacterial properties, and the activity of these layers inhibited the biofilm formation and eradicated mature biofilms of Gram-positive Staphylococcus aureus and Enterococcus faecalis, as well as, Gram-negative Pseudomonas aeruginosa and Escherichia coli bacterial strains. Overall, the microstructure-related oxygen diffusivity of the layers and the water stability of the complexes were the most critical parameters for the efficient and durable use. These photoactive layers are attractive for the design of antibacterial surfaces activated by visible light and include additional functionalities such as the conversion of harmful UV/blue light to red light or oxygen sensing.
Keywords: komplexní sloučeniny; electrophoretic deposition; phototoxicity; luminescence; Molybdenum; biofilm; Glass; fotosenzibilizující látky; Light; sklo; singlet oxygen; singletový kyslík; Coordination Complexes; Biofilms; Singlet Oxygen; molybden; Escherichia coli; Staphylococcus aureus; Photosensitizing Agents; Enterococcus faecalis; molybdenum cluster complex; světlo; biofilmy